The central subgroup of the nonabelian tensor square of a torsion free space group - Mohammad, S. A. (American Institute of Physics Inc., 2016)
Space groups of a crystal expound its symmetry properties. One of the symmetry properties is the central subgroup of the nonabelian tensor square of a group. It is a normal subgroup of the group which can be ascertained by finding the abelianisation of the group and the nonabelian tensor square of the abelianisation group. In this research, our focus is to explicate the central subgroup of the nonabelian tensor square of the torsion free space groups of a crystal which are called the Bieberbach groups.